Procedure for Handling 4-H Accounts: Guidelines for Fund-Raising - Marilyn N. Norman; Joy C. Jordan (EDIS, 2008)
Revised! 4H5.5, a 4-page fact sheet by Marilyn N. Norman and Joy C. Jordan, gives guidelines for properly conducting fundraising within 4-H. Revised to reflect policy changes. Published by the UF Department of Family, Youth and Community Sciences, January 2008.